Goodness-of-fit versus significance: A CAPM selection with dynamic betas applied to the Brazilian stock market - André Ricardo de Pinho Ronzani; Osvaldo Candido; Wilfredo Fernando Leiva Maldonado (International Journal of Financial Studies, 2017)
In this work, a Capital Asset Pricing Model (CAPM) with time-varying betas is considered. These betas evolve over time, conditional on financial and non-financial variables. Indeed, the model proposed by Adrian and Franzoni (2009) is adapted to assess the behavior of some selected Brazilian equities. For each equity, several models are fitted, and the best model is chosen based on goodness-of-fit tests and parameters significance. Finally, using the selected dynamic models, VaR (Value-at-Risk) measures are calculated. We can conclude that CAPM with time-varying betas provide less conservative VaR measures than those based on CAPM with static betas or historical VaR.
Keywords: C32; G12; 330; dynamic models; Kalman filter; time-varying beta; CAPM; VaR